Hemoglobin Indianapolis (beta 112[G14] arginine). An unstable beta-chain variant producing the phenotype of severe beta-thalassemia. - Adams, J G (1979)
Hemoglobin (Hb) Indianapolis is an extremely labile beta-chain variant, present in such small amounts that it was undetectable by usual techniques. Clinically, it produces the phenotype of severe beta-thalassemia. Biosynthetic studies showed a beta:alpha ratio of 0.5 in reticulocytes and about 1.0 in marrow after a 1-h incubation. These results, similar to those seen in typical heterozygous beta-thalassemia, suggested that betaIndianapolis was destroyed so rapidly that its net synthesis was essentially zero. To examine the kinetics of globin synthesis, reticulocyte incubations of 1.25--20 min were performed with [3H]leucine. The betaIndianapolis:beta A ratio at 1.25 min was 0.80 suggesting that beta Indianapolis was synthesized at a near normal rate. At 20 min, this ratio was 0.46 reflecting rapid turnover of beta Indianapolis. The erythrocyte ghosts from these incubations contained only betaIndianapolis and alpha-chains, and the proportion of betaIndianapolis decreased with time, indicating loss of betaIndianapolis. Pulse-chase studies showed little change in beta A:alpha ratio and decreasing betaIndianapolis:alpha and betaIndianapolis:beta A with time. The half-life of betaIndianapolis in the soluble hemoglobin was approximately equal to 7 min. There was also rapid loss of beta Indianapolis from the erythrocyte membrane. From these results, it may be inferred that betaIndianapolis is rapidly precipitated from the soluble cell phase to the membrane, where it is catabolized. Heterozygotes for beta 0-thalassemia usually have minimal hematologic abnormalities, whereas heterozygotes with betaIndianapolis, having a similar net content of beta-chain, have severe disease. The extremely rapid precipitation and catabolism of betaIndianapolis and the resulting excess of alpha-chains, both causing membrane damage, may be responsible for the severe clinical manifestations associated with this variant. It seems likely that other, similar disturbances in the primary sequence of globin polypeptide chains may produce clinical findings similar to those seen with hemoglobin Indianapolis and thus produce the phenotype of severe beta-thalassemia.